Vasculitis: Decade in Review - Demir, Selcan; Sönmez, Hafize E.; Özen, Seza (Current Rheumatology Reviews, 2019)
Background: In the last decade, we have come to better understand and manage the vasculitides. The classification of vasculitides has been revised. Genome- wide association studies and linkage analyses have been undertaken in hope of better understanding the pathogenesis of vasculitides. Comprehensive genetic studies have highlighted new pathways that may guide us in more targeted therapies. Description of the monogenic forms of vasculitis, such as deficiency of adenosine deaminase type 2 (DADA2), Haploinsufficiency of A20 (HA20), have introduced a new perspective to vasculopathies, and introduced alternative treatments for these diseases. Conclusion: In this review, the important discoveries in pathogenesis and consensus treatment recommendations from the past decade will be summarized.
Keywords: treatment